Operational efficiencies of six microwave based extraction methods for orange peel oil. (January 2019) - Razzaghi, Seyed Elyas; Arabhosseini, Akbar; Turk, Mohammad; Soubrat, Thibault; Cendres, Aurélie; Kianmehr, Mohamad Hosein; Perino, Sandrine; Chemat, Farid
Abstract: Microwave is a very efficient energy carrier for the extraction of essential oils from aromatic plants in unit operations intended for distillation. The aim of this work was to compare six extraction processes: four Microwave Assisted Extraction (MAE) and two conventional processes for the extraction of orange essential oils. The comparison was based on different processing and qualitative criteria such as extraction yield, power efficiency, biochemical and sensorial attributes. Two multiple criteria methods were developed to select the most efficient process. The first method is based on the income over energy cost index. The results show that among the set of extraction processes studied only Microwave Hydrodiffusion and Gravity (MHG) would be operational cost efficient. The second method combines both processing and qualitative criteria. The results show that the extraction processes with combination of microwaves and steam are best ranked followed by those with just microwaves. Highlights: Orange essential oils were extracted using six extraction processes. Productivity, power efficiency, chemical and sensory analysis were carried out. Two multi-criteria methods were proposed to select and optimize the most suitable method. Essential oil microwave extraction is an economically viable solution.